Classical massage in multiplesclerosis. - Santos, Iara; Laurito, Gabrielle Stephanie Soares; Silva, Maria Nazaré Soares; Carruba, Marcelo; Leal, Andrea Fernanda; Barcala, Luciana (Manual Therapy, Posturology & Rehabilitation Journal, 2015)
Background: Multiple sclerosis is an autoimmune disease, inflammatory that affects the white matter of the central nervous system, resulting in neurological signs and symptoms that after the outbreaks, may leave sequels as the location of the lesion. Symptoms may include loss of double vision, muscle weakness, lack of balance, numbness, pain, problem in the control of the bladder and bowel, fatigue, emotional changes and intellectual impairment. Objective: To describe the effects and compromise in carrier of multiple sclerosis, to check the efficiency of classical massage in reduction of symptoms and their influence on the performance of activities of daily living. Method/Design: It is a study of controlled clinical trial with a convenience sample of individuals already framed in clinical school of physical therapy at the University Nine July (Uninove). Eight were selected individuals diagnosed with Multiple Sclerosis, between 30 and 50 years of age, without dermatological problems for the application of classical massage. The subjects were evaluated before and after the proposed intervention consists of 20 sessions of classical massage performed twice a week having a duration of 40minutes each session. Results: In the first three months, there have been significant results demonstrated the functional assessment (MIF), but from the sixth to the twelve months remained functional stability. The quality of life (SF-36) showed that in pre-requirements of General Condition, Vitality, Social, Emotional and Mental, was increased in the first nine months and after this period, the results were not significant. In the evaluation of the balance by the scale of Berg in the first three months did not show satisfactory results, but from the third month to the sixth month there was a significant increase in the balance. The sensitivity surface showed an increase after the sixth month of application of classical massage, keeping up to twelve months proposed by the study. In profound sensitivity presented significant results from nine months of treatment. Conclusions: The present study showed that the physical therapy, through the classical massage, does not eliminate the neurological damage that attends the disease, but can act in the treatment of specific symptoms favoring the well-being and the features of patients with multiple sclerosis.